Macrocyclic Azopyrrole: Synthesis, Structure and Fluoride Recognition - Ying An; Ying Sun; Zhenming Yin (Organics, 2025)
A macrocyclic receptor based on azopyrrole and polyether was synthesized, and its structure was characterized by NMR (1H and 13C), HRMS and X-ray crystallography. In the solid state, the macrocyclic molecules could bind methanol through a pair of N-H…O hydrogen bonds and further self-assembled into tubular structures through C-H…N hydrogen bonds. This revealed that the crystal could still keep its porous properties after the included molecules were removed. The UV–Vis titration indicates that the macrocylic receptor can chromogenically and selectively sense fluoride ion in DMSO solution, and the sensing mechanism was rationalized by 1H NMR.